Characterization Analysis in Abdurrahman Munif’s Sibaq al-Masafah al-Thawilah (Long-Distance Race) - Mohammed Eid A Alotaibi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
The research aims to study character building in Abdul Rahman Munif's novel The Long Distance Race. The writer has sought to convey his novelistic characters through narrative and creative ways, such as using multiple patterns to highlight its varied qualities and features. His study used the structural approach, but benefited from other critical techniques as necessary given the study's nature. The investigation found several key findings, including: First, the narrator does not reveal most of the novelistic characters' traits, but rather those that serve the story's circumstances and goals. Because the narrator depended on presenting the physical component in two ways: telling and showing, it is vital in establishing the primary character. Second: The physical dimension is an important part in building the main character. Third, the psychological component shows us the personality's psychological states, emotions, and feelings, as seen in the psychological battle that the hero Peter has with Bashir, and how he attempts to avoid falling in love with her and racing towards her. Fourth, the writer elected to blend the two narrators, resulting in a mixed vision called dual vision. Fifth, the novel's writer did not give the character the role of showing himself. Most of the characters have suggestive implications, manifested via their position and direction in the world of narration, thereby forging the connection between the meaning of the character's name and the path of the novel's events.ÙŠÙ‡Ø¯Ù Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø¯Ø±Ø§Ø³Ø© Ø¨Ù†Ø§Ø¡ Ø§Ù„Ø´Ø®ØµÙŠØ© ÙÙŠ Ø±ÙˆØ§ÙŠØ© Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙ…Ù† Ù…Ù†ÙŠÙ